Efficacy of Stream Sediment Survey in delineating geochemical halos: A case study of well and non-shed areas in the Gambe-Tola Baryte District, Northeastern Nigeria - Halilu, Maimuna (IJRDO-Journal of Applied Science, 2017)
The efficacy of stream sediment survey in delineating geochemical halos is assessed in theGambe-Tola Area of Northeastern Nigeria. Well-shed area had a higher statistical probability ofbeing associated with geochemical halos synonymous with elevated concentrations in the rockswhereas less shed shed areas sometimes showed little or no correlation to elevatedconcentrations in the rocks. Efforts to trace known Baryte mineralization in the area throughgeochemical halos from stream sediment was unsuccessful as the mineralized areas were notwell shed, due to large dispersion distance at sampling and natural solubility of BaSo4 in water.